PEMBINAAN DISIPLIN KERJA PEGAWAI DI UNIT PENGEMBANGAN PRODUKTIVITAS DAERAH DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI KALIMANTAN BARAT - Ela Septi Larasati E.42009077 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This thesis aims to determine and analyze corrective disciplinary coaching methods in Regional Productivity Development Unit Manpower and Transmigration Office of West Kalimantan Province. To analyze the data that has been obtained, the researchers used qualitative methods, with the intent that the researchers in finding the facts using logical reasoning to describe, explain, and elaborate systematically of phenomena encountered in the use of words, sentences to derive conclusions and suggestions are needed. The title of this essay chosen after seeing the phenomena in the field that is still less than optimal coaching discipline work done by the leader because the leader is considered less strict and prudent in taking sanctions action performed by employees who commit disciplinary offenses. Based on the phenomenon of the issues discussed in this paper is to describe the method of discipline is corrective coaching conducted by Regional Productivity Development Unit in the Department of Manpower and Transmigration of West Kalimantan Province. This study used a qualitative approach with descriptive research method. Results of research that has been done is still the sanctions have not been made by the head of Regional Productivity Development Unit Manpower and Transmigration Office of West Kalimantan Province remember until now there is no discipline employees who violate the disciplinary action that can be based on the stage sanctions that have not been implemented. Therefore, coaching employees one way to control of the leader to be much higher in order to increase employee discipline. Keyword: Discipline, Corrective Discipline Coaching Method